Practices and Profiles of Management Staff for Innovation and Change Management in Costa Rican Educational Centers (Innovaciones Educativas, 2025)
Contemporary change processes require management staff to assume a proactive role in promoting innovation and school change. Therefore, this study aimed to analyze the practices and profiles of change management implemented by principals of educational centers under the Regional Directorate of Education of Los Santos, part of the Ministry of Public Education of Costa Rica. A quantitative methodological approach was adopted, with a non-experimental, cross-sectional design and exploratory scope. The sample consisted of 67 principals selected through simple random sampling. Furthermore, a questionnaire validated by expert judgment and with a reliability of α = 0.81 was applied. Exploratory factor analysis (KMO = 0.928; p < 0.001) revealed two factors explaining 80% of the variance: leadership oriented towards a culture of innovation and evidence- and evaluation-based change management. On the other hand, cluster analysis identified three management profiles: those who drive partial transformations, those who implement strategic and innovative changes, and those who have barely initiated change processes or have not implemented them. Finally, the findings highlight the need to strengthen continuous professional development processes for management staff, as well as to promote greater flexibility in the regulatory framework, so that change management processes become institutionalized and contribute to transforming school dynamics according to the needs of the context.
Keywords: educational leadership; school management; educational innovation; change management; management profiles